Affine Isoperimetric Type Inequalities for Static Convex Domains in Hyperbolic Space (Journal of Mathematical Study, 2025)
In this paper, the notion of hyperbolic ellipsoids in hyperbolic space is introduced. Using a natural orthogonal projection from hyperbolic space to Euclideanspace, we establish affine isoperimetric type inequalities for static convex domains inhyperbolic space. Moreover, equality of such inequalities is characterized by thesehyperbolic ellipsoids.